PERAN NILAI-NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER BANGSA DI ERA DIGITAL - Iqbal, Muhammad; Lumbantoruan, Ruth; Tondang, Ocha; Sitanggang, Hertati; Sari, Alpida; Ronauli, Anggun; Bangun, Shaniya (Jurnal Merah Putih Sekolah Dasar, 2025)
The digital era has significantly transformed social interactions, learning processes, and character formation, particularly among younger generations. As the ideological foundation of the Indonesian state, Pancasila plays a crucial role in guiding moral values and strengthening national character amid rapid technological development and globalization. This study aims to analyze the role and relevance of Pancasila values in building national character in the digital era, as well as the challenges faced in their implementation. The research employed a qualitative approach using a literature review method by examining books, scientific journals, and relevant academic documents related to Pancasila, character education, and digital society. The findings indicate that the values of Pancasila—belief in God, humanity, unity, democracy, and social justice—remain highly relevant as ethical guidelines for digital behavior, particularly in addressing issues such as digital ethics, cyberbullying, misinformation, and declining social awareness. The study also highlights the importance of integrating Pancasila-based character education within educational institutions to foster responsible, ethical, and socially aware digital citizens. Therefore, collaboration among government, educational institutions, and society is essential to internalize Pancasila values through character education and positive utilization of digital technology.